Assessing the Perceived Value of Neuroethics Questions and Policy to Neuro-Entrepreneurs - Moss, Ankita U.; Li, Zone R.; Rommelfanger, Karen S. (Frontiers in Neuroscience, 2021)
Neuroscience and its findings have deep personal and cultural meaning, so the implications of brain science raise new flavors of ethical issues not covered by traditional bioethics. The field of neuroethics bridges this gap, addressing and responding to the ethical, legal, and social issues intimately related to the evolving landscape of neuroscience. Neuroethical concerns have registered at the highest levels of government. In 2018, an interdisciplinary global neuroethics group working with leading scientists from the International Brain Initiative, a consortium of 7 large-scale national-level brain research projects around the globe, published “Neuroethics Questions to Guide Ethical Research in the International Brain Initiatives”. The document provides guiding questions to consider throughout the lifecycle of neuroscience research. These questions tackle issues such as identity, morality, cross-cultural differences, privacy, and potential stakeholder involvement in ethical decision-making. In our work with the International Brain Initiative, we noted the important role that the private sector will play in translating and scaling neuroscience for society. We also noticed a gap in communication and collaboration between government, academia and the private sector. These guiding questions were largely co-created with policy makers and academics, so it was unclear how these issues might be received by neuro-entrepreneurs and neuro-industry. We hoped to identify not only common concerns, but also a common language for discussing neuroethical issues with stakeholders outside of government and academia. We used empirical ethics methods to assess the perceived value and attitudes of neuro-entrepreneurs toward neuroethical issues and whether or not these issues align with the process of neuro-innovation. We conducted one-on-one structured interviews with 21 neuro-entrepreneurs in the private sector and used two independent reviewers to analyze for themes. From this preliminary research, we identified key neuroethical themes and processual pain points of neurotech entrepreneurs throughout the innovation process. We also provide a preliminary neuroethics needs assessment for neuro-industry and suggest avenues through which neuroethicists can work with neurotech leadership to build an ethically aligned future. Overall, we hope to raise awareness and provide actionable steps toward advancing and accelerating societally impactful neuroscience.